IMPLEMENTASI MODEL RATIONAL UNIFIED PROSES (RUP) PADA APLIKASI PENGELOLAAN OPERASIONAL PDAM KAPUAS BERBASIS WEB - Subandi; Hidayat, Muhammad (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2024)
This study investigates how to implement the Rational Unified Process (RUP) model in the web-based operational management application of PDAM Kapuas. The aim of this research is to improve operational efficiency, optimize resource utilization, and enhance customer satisfaction. The research method involves collecting relevant data, analyzing system requirements, designing software architecture, developing prototypes, and evaluating the implementation of the Rational Unified Process (RUP). RUP employs an iterative approach and allows for diverse roles among team members and resource optimization. Inception, Elaboration, Construction, and Transition are the stages of RUP development. The results of this research include the analysis of business processes, creation of use case diagrams, design of class diagrams, and development of 27 application interfaces that facilitate access to each menu. The implementation of the RUP methodology